2020
DOI: 10.1037/xap0000269
|View full text |Cite
|
Sign up to set email alerts
|

Action bias in the public’s clinically inappropriate expectations for antibiotics.

Abstract: Translational Abstract (150 -250 words)When people want antibiotics from their physician it encourages the physician to prescribe them, even if it is not clinically appropriate. Clinical guidelines recommend that physicians educate their patients about illnesses and antibiotics to eliminate any inappropriate desires for antibiotics. We tested whether providing clinical information to educate patients can completely eliminate inappropriate desires for antibiotics and whether a set of cognitive biases could expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Our findings are aligned with existing research that educational interventions may reduce desires for antibiotics (Madle, Kostkova, Mani‐Saada, Weinberg, & Williams, 2004; Price et al, 2011; Roope et al, 2020; Thorpe et al, 2020a; Thorpe, Sirota, Juanchich, & Orbell, 2020b), but offer a distinct contribution by controlling for illness characteristics (severity and duration) and indicating that physicians might be empowered to change patient expectations during a consultation in which antibiotics are clinically inappropriate by providing information that specifically addresses ineffectiveness of antibiotics for the condition presented, and their side effects. Providing both illness and antibiotic information is recommended by NICE guidelines (PHE, 2017), and it is important to clarify that based on these findings we do not believe or recommend that physicians should not provide information on illness aetiology.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings are aligned with existing research that educational interventions may reduce desires for antibiotics (Madle, Kostkova, Mani‐Saada, Weinberg, & Williams, 2004; Price et al, 2011; Roope et al, 2020; Thorpe et al, 2020a; Thorpe, Sirota, Juanchich, & Orbell, 2020b), but offer a distinct contribution by controlling for illness characteristics (severity and duration) and indicating that physicians might be empowered to change patient expectations during a consultation in which antibiotics are clinically inappropriate by providing information that specifically addresses ineffectiveness of antibiotics for the condition presented, and their side effects. Providing both illness and antibiotic information is recommended by NICE guidelines (PHE, 2017), and it is important to clarify that based on these findings we do not believe or recommend that physicians should not provide information on illness aetiology.…”
Section: Discussionsupporting
confidence: 88%
“…While some theoretical consideration has been applied to physician’s beliefs regarding antibiotic use (Donald, 2016), we believe this is the only study to have systematically examined the influence of prior knowledge alongside illness representations and treatment beliefs on the cognitive and motivational mechanisms underlying inappropriate expectations and requests for antibiotics. In the light of recent work assessing the effect of different combinations of messaging on inappropriate antibiotic expectations (Roope et al, 2020; Thorpe et al, 2020a, 2020b), the current research provides important causal evidence for the effect of specific types of clinical information provision on inappropriate antibiotic expectations and requests.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…5,6 Ritov and Baron 5 first identified the omission bias for vaccine decisions, and many studies since have found that the bias toward inaction predominates for health decisions, 7 including vaccination, [8][9][10][11][12][13][14][15][16] medication, 14,17,18 and acute care decisions. 19,20 The less common tendency to err on the side of action is not unique to cancer and has been found for other health conditions, [20][21][22] but cancer does seem to particularly engage that tendency both for screening and for treatment. 4,[23][24][25] While ''do no harm'' may be a guiding principle for many health decisions, ''do whatever it takes,'' may be a prevailing perspective for cancer.…”
Section: Overlooking Risk Probabilitiesmentioning
confidence: 99%
“…For example, illness incoherence-being puzzled by the nature of an illness-predicted people's expectations of antibiotics for their recently experienced coldlike symptoms (Thorpe et al, 2021). Robust experimental evidence also showed that reducing laypeople's diagnostic uncertainty-by providing a family physician's clinical judgment about viral etiology of the symptoms, sometimes even accompanied by a diagnostic test pointing in the same direction-substantially decreased people's expectations of antibiotics in hypothetical consultations (Thorpe et al, 2020a(Thorpe et al, , 2020b(Thorpe et al, , 2021.…”
mentioning
confidence: 99%